Peran Kurikulum OBE untuk Pengembangan Manusia Pertahanan Unggul di Era VUCA - Anindito (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2024)
The VUCA era has presented significant challenges in the development of defense human resources, especially in the field of information technology. This study analyzes the implementation of the Outcome-Based Education (OBE) curriculum in the Informatics Undergraduate Study Program at the Indonesian Defense University (Unhan RI) in forming superior defense humans. Using a qualitative approach with a case study method, this study explores the effectiveness of OBE in developing the competencies needed to face the challenges of the VUCA era. The results of the study indicate that the implementation of the OBE curriculum has a positive contribution in producing graduates who have adaptive abilities in dealing with cyber threats and changes in defense technology. This success is reflected in the achievement of learning outcomes that are relevant to national defense needs, especially in the aspects of cyber defense and defense technology. Recommendations for development include strengthening the integration of the latest technology and increasing international cooperation to broaden learning perspectives.